Assessment of lactation curve parameters for test-day Milk yield, Fat% and SNF% in Murrah Buffalo - Verma, Uma Kant; Vohra, Vikas; Gupta, I D; Verma, A; Mukherjee, A; Deb, S M (Indian Journal of Dairy Science, 2020)
A lactation curve can reveal abundant information about the pattern and persistency of lactation in an individual dairy animal. Identifying buffalo with particular pattern and persistency of lactation milk yield can serve as additional selection criterion for a dairy herd. Wood’s incomplete gamma function fitted well to the monthly test-day milk, fat% and SNF% yields of Murrah buffaloes and can be used in prediction of milk and milk constituents yield with higher accuracy. We also report that exponential function (Wilminks model) also can be used in prediction of milk constituents in Murrah buffaloes when constant k is changed in the model from 0.05 to 0.06 or 0.07. Thus, these functions can be used to make breeding and management related decisions particularly selection of desired and persistent buffaloes and thus improving the production of the herd by culling non-desired type of Murrah buffaloes.